(Stop) Deporting Pegah: Sovereignty, (Public) Sex, and (Life)/Death - Masoumi, Azar (Social justice, 2016)
This article reads the highly publicized lesbian refugee case of Pegah Emambakhsh in the UK to argue that the practice of sovereignty, particularly in relation to sexual minority refugees, is a deeply sexual practice. I draw on queer theory and theories of biopolitics and necropolitics to argue that sovereignty and sex are linked through a politics of death and terror. My reading of Emambakhsh's refugee case demonstrates how these linkages can be traced within state asylum adjudication processes.